Prikaz treh primerov vadbe hoje z napravo E-go pri osebah po preboleli možganski kapi - Bizovičar, Nataša (Rehabilitacija (Ljubljana), 2015)
Introduction: Balance and walking ability are often affected in patients after stroke. Engineers at the University Rehabilitation Institute in Ljubljana developed a prototype of a device for dynamic balance training during over-ground walking (E-go). The E-go device comprises a mobile platform attached to the supporting mechanism that enables adjustable mechanical pelvis support in the transversal plane. The speed and direction of the E-go device is controlled by the therapist. The aim of the study was to evaluate the usefulness and effectiveness of the E-go device in patients after stroke. Methods: The study included three patients: a 49- in and a 55-year-old female (1 month and 5 months after intracerebral haemorrhage, respectively) who underwent gait training for 3 weeks with the E-go device, followed by 3 weeks of gait training within regular physiotherapy programmes. A 65-year-old man (6 months after ischaemic stroke) underwent gait training first within regular physiotherapy programmes and then with the E-go device (both for 3 weeks). We assessed walking ability, balance and lower limb function with various clinical tests: Fugl-Meyer Assessment for lower extremity, Berg Balance Scale, Functional Ambulation Classification, Postural Assessment Scale for Stroke patients and Romberg%s test. Results: After 6 weeks of training, all the patients improved their walking distance, walking speed and balance. The first female patient and the male patient also had better results on the Fugl-Meyer Assessment for lower extremity, but there were no differences for the second female patient. Conclusions: The use of the E-go device was a useful method in one of the female patients and the male patient, improving their walking and balance function. Due to pronounced hemiparesis, training with the E-go device was not appropriate for the second female patient % it was difficult for the therapist to control the device and to guide the patient during walking at the same time.
Keywords: E-go robotic device; fizioterapija; Gait; hoja; možganska kap; Physical Therapy Modalities; physiotherapy; rehabilitacija; rehabilitation; robotska naprava E-go; Stroke; vocational rehabilitation